Proposal of a Pharmacotherapy Update Seminar on Hypertension - Ana María Ramos Cedeño; Rubén Darío García Núñez; Regla Lisbel López Guerra; Odalys Miraz Concepción; Paula Rodríguez Sánchez; Martín O. Peralta Rodríguez (Centro Provincial de Información de Ciencias Médicas. Cienfuegos, 2014)
Because of the impact of hypertension on morbidity and mortality rates worldwide, it represents a challenge for Primary Health Care. In recent years a complete therapeutic arsenal of demonstrated efficacy has been developed; however, the results expected with treatment have not been achieved, at least in terms of population. Hence, researchers in this field make endless efforts to solve this health problem and the complications resulting from it. One way to overcome this situation is to keep medical staff updated and to promote students' prescriptive scientific thinking. That is the reason why, we propose a method to develop pharmacotherapy update seminars, taking hypertension as example.